Girls’ engagement with technology education: A scoping review of the literature - Sultan, Ulrika; Axell, Cecilia; Hallström, Jonas (Design and Technology Education: An International Journal, 2019)
The aim of this study is to review internationally published scientific literature on the subject of girls’ engagement in technology education, in order to identify the most common descriptions of girls’ engagement with technology education, girls’ technological activities, and the relationship between girls and technology. After a scoping review of the literature, 20 relevant articles were identified and included in the study; they were analysed using content analysis. The results show that, according to the reviewed studies, girls are less interested in and have less positive attitudes towards technology (education) than boys. They are also less likely to choose a technology- or STEM-oriented occupation. Several of the included studies venture possible explanations as to why this is and refer mainly to cultural factors. Those studies that do define the type of technology used in girls’ activities mostly describe a neutral, or male kind of “nuts and bolts” technology. As regards girls’ relationship to technology, there is potential for improving female engagement using apparently simple means; for example, making sure the social context of teaching is adapted to girls. The results of the literature review are discussed in terms of their implications for future research and can be used as a guide for educators and researchers in the area. In particular, the reasons for girls’ lower interest in technology education compared to boys need to be further researched, and it may be that researchers need to study girls in their own right, not in perpetual comparison with boys, in order to come closer to an answer.